The Effect of Malang City Regional Regulation on Increasing Regional Income - Rahayu, Karina Widya (Journal of Transformative Governance and Social Justice, 2024)
This research aims to analyze the influence of Regional Regulation Number 4 of 2023 on increasing local original income in Malang City for the 2021-2023 period. Data was obtained from the Malang City Regional Financial and Asset Management Agency. The research method used in this writing is a qualitative approach with a focus on literature study. Data and information are obtained from official documents, scientific journals and related financial reports. In this research, the author explores an understanding of the impact of Regional Regulation Number 4 on Regional Original Income (PAD) in Malang City through literature analysis and the context of the applicable regulations. Based on the results of the analysis of the influence of Regional Regulation Number 4 of 2023 on Increasing Original Regional Income in Malang City for the 2021-2023 period, it shows a consistent increase in PAD, which can be attributed to various factors including the implementation of Regional Regulation Number 4 of 2023. Overall, Regional Regulation Number 4 of 2023 is expected will have a positive impact on increasing PAD in Malang, not only strengthening fiscal autonomy but also supporting sustainable and inclusive development.